Carbon electrode engineering for high efficiency all-inorganic perovskite solar cells. Issue 21 (26th March 2020) - Mi, Longfei; Zhang, Yan; Chen, Taotao; Xu, Enze; Jiang, Yang
Abstract : A carbon/CNT/MXene mixed electrode in CsPbBr3 solar cells provides a network structure and multi-dimensional charge transfer path, which effectively increases the conductivity of the carbon electrode and carriers transport. Abstract : Carbon-based inorganic perovskite solar cells (PSCs) have demonstrated an excellent performance in the field of photovoltaics owing to their simple fabrication techniques, low-cost and superior stability. Despite the lower efficiency of devices with a carbon electrode compared with the conventional structure, the potential applications in large scale have attracted increasing attention. Herein, we employ a mixed carbon electrode inorganic PSC by incorporating one-dimensional structure carbon nanotubes (CNTs) and two-dimensional Ti3 C2 -MXene nanosheets into a commercial carbon paste. This mixed carbon electrode, which is different from the pure carbon electrode in showing a point-to-point contact, provides a network structure and multi-dimensional charge transfer path, which effectively increases the conductivity of the carbon electrode and carriers transport. A respectable power conversion efficiency of 7.09% is obtained through carbon/CNT/MXene mixed electrode in CsPbBr3 -based solar cells.